Medical image analysis - Dhawan, Atam P.; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2011)
The expanded and revised edition will split Chapter 4 to include more details and examples in FMRI, DTI, and DWI for MR image modalities. The book will also expand ultrasound imaging to 3-D dynamic contrast ultrasound imaging in a separate chapter. A new chapter on Optical Imaging Modalities elaborating microscopy, confocal microscopy, endoscopy, optical coherent tomography, fluorescence and molecular imaging will be added. Another new chapter on Simultaneous Multi-Modality Medical Imaging including CT-SPECT and CT-PET will also be added. In the image analysis part, chapters on image reconstruc.
Image Formation -- Interaction of Electromagnetic Radiation with Matter in Medical Imaging -- Medical Imaging Modalities: X-Ray Imaging -- Medical Imaging Modalities: Magnetic Resonance Imaging -- Nuclear Medicine Imaging Modalities -- Medical Imaging Modalities: Ultrasound Imaging -- Image Reconstruction -- Image Processing and Enhancement -- Image Segmentation -- Image Representation, Analysis, and Classification -- Image Registration -- Image Visualization -- Current and Future Trends in Medical Imaging and Image Analysis.
Print version record.
Keywords: Diagnostic imaging; Imaging systems in medicine; Diagnostic imaging; Imaging systems in medicine; Electronic books